Climate-smart soil water and nutrient management options in semiarid West Africa: a review of evidence and analysis of stone bunds and zaï techniques - Zougmoré, Robert B.; Jalloh, Abdulai; Tioro A (Springer, 2014)
There is an increasing need for West African Sahel farmers to be availed with appropriate technologies and management practices that sustainably increase productivity and resilience, while reducing greenhouse gas emissions where possible. In this paper, we analysed prevailing key water and nutrient interaction practices namely stone bund, zaï and half-moon techniques in order to explore how their outcomes could be linked to climate change adaptation and mitigation. Data were derived from previous publications but were reinterpreted in the angle of technologies’ alignment with the three pillars of climate-smart agriculture (CSA). We found that the most successful systems are those that provide water, nutrients and a supportive soil structure in a synergistic manner. Indeed, technologies such as zaï, half-moons and stone bunds, combined with an application of organic/inorganic sources of nutrients, are promising climate-smart agricultural practices that could be widely used by smallholder farmers to maintain food production and secure farmers’ livelihoods, while contributing to ecosystem services. However, accompanying incentive measures are needed to empower and capacitate rural farmers to adopt the considered techniques. These are successful examples that can form the basis for informing farmers and agricultural extensionists, as well as future agricultural development plans, policies and investments that pursue sustainable food and nutritional security in the West African Sahel.